Vocational orientation in Costa Rica: strategies and actions towards the educational challenges caused by the COVID-19 pandemic - Arce Valerio, Ileana [Verfasser] (My University, 2022)
“One factor in the quality of the Costa Rican educational system is the National Guidance Service which focuses its work on enhancing the integral development of the student population from the educational, vocational, and personal-social components. In 2020 and 2021, due to the COVID-19 pandemic, challenges have arisen for the development of educational processes and the scholastic link, which has led to the need to strengthen strategies and actions related to vocational guidance, with lines of work that allow continuity through blended learning and that accompany students and their families in their educational tasks through inputs that respond to their respective educational scenarios.” (author’s abstract; BIBB-Doku)
Keywords: I 2.3.3 Lateinamerika; 370; Berufsbildung; Pandemie; Auswirkung; Costa Rica